Predictors of fitness status on success in taekwondo - Cular, D.; Krstulovic, S.; Katic, R.; Primorac, D.; Vucic, D. (Collegium Antropologicum, 2013)
The aim of this research was to determine the order and importance of particular fitness status variables impact on success in taekwondo according to opinions of top taekwondo instructors (experts). Partial objectives included analysis of metric characteristics of the measuring instrument, and determining differences between two disciplines (sparring and technical discipline of patterns) and two competition systems (WTF and ITF). In accordance with the aims, the research was conducted on a subject sample which consisted of 730 taekwondo instructors from 6 continents and from 69 countries (from which we selected 242 instructors), who are at different success levels in both taekwondo competition systems (styles) and two taekwondo disciplines. The respondents were divided into 3 qualitative subsamples using a dependent variable of the instructor`s accomplished results. In 6 languages, they electronically evaluated, in percentage value (%), the impact of 8 motor and functional abilities: specific strength (STR), flexibility (FLX), specific endurance (END), speed (SPE), balance(BAL), coordination (COO), agility (AGI) and accuracy (ACC). The analysis of metric characteristics of the constructed instrument showed a satisfactory degree of agreement (IIr) which is proportional to the level of respondent quality, i.e. it grows along with the increase in instructor quality in all analyzed disciplines of both systems. According to the obtained results, speed and specific endurance were ranked as the abilities which are most important for success in the sparring discipline in both competition systems (WTF and ITF), whose instructors also expressed a higher level of agreement in relation of speed and success in the technical disciplines.